The Role of The Teacher in Building Intercultural Communication Skills in Foreign Language Teaching: Teachers' Views with Examples from France and Turkey - Gizem Köşker; Gülnihal Gülmez (Anı Publishing, 2018)
Globalization and communication technologies are making intercultural communication necessary in international platform. Individuals need some skills to communicate effectively. Current foreign language teaching programs need to be prepared with the practices aimed at building intercultural communication skills. As in every educational process, the teacher is the most responsible person in teaching these skills. To identify and compare views of foreign language teachers on the teacher's role in building intercultural communication skills in foreign language teaching, and to collect data, twenty teachers from two universities of France and Turkey were asked to complete an open-ended questionnaire and followed one by one interview. The ethnic and cultural diversity enabled us to make comparisons among different perspectives. The analysis revealed that all participants developed awareness about importance of intercultural communication, yet experienced difficulties in planning intercultural activities and covering them in actual lessons. It was revealed that none of the participants had received any special training on intercultural communication. Some different views of participants that emerged, as a result of this study, are attributed to their cultural codes.